2010
DOI: 10.1111/j.1460-9592.2010.03408.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of droperidol and ondansetron on dispersion of myocardial repolarization in children

Abstract: Droperidol and ondansetron, in therapeutic anti-emetic doses, produce equivalent, clinically insignificant QT prolongation and negligible Tp-e prolongation, suggesting that neither is torsadogenic in healthy children at these doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 29 publications
1
13
0
2
Order By: Relevance
“…10 Mehta et al conducted a study that was published in 2010 to compare the effects of droperidol and ondansetron on the QT interval in children. 11 One hundred and eight children undergoing elective outpatient surgery were randomized to receive droperidol at 20 mcg/kg, ondansetron at CABG = coronary artery bypass grafting; CAD = coronary artery disease; CHF = congestive heart failure; COPD = chronic obstructive pulmonary disease; F = female; HB = heart block; H/o = history of; ICD = implantable cardiac defibrillator; LVAD = left ventricular assist device; M = male; MVR = mitral valve repair; PVC = premature ventricular contraction; VT = ventricular tachycardia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Mehta et al conducted a study that was published in 2010 to compare the effects of droperidol and ondansetron on the QT interval in children. 11 One hundred and eight children undergoing elective outpatient surgery were randomized to receive droperidol at 20 mcg/kg, ondansetron at CABG = coronary artery bypass grafting; CAD = coronary artery disease; CHF = congestive heart failure; COPD = chronic obstructive pulmonary disease; F = female; HB = heart block; H/o = history of; ICD = implantable cardiac defibrillator; LVAD = left ventricular assist device; M = male; MVR = mitral valve repair; PVC = premature ventricular contraction; VT = ventricular tachycardia.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the study's findings, the authors concluded that droperidol and ondansetron are highly unlikely to increase the risk of torsades in healthy pediatric patients. 11 We identified a number of limitations with this retrospective safety study, including: the inability to capture brief episodes of polymorphic VT with a 12-lead electrocardiogram, correct diagnosis of the event, or technical issues with how the database extracted its data. To eliminate bias we relied on documented medical provider diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] Other studies reported efficacy of the drug in pediatric surgical or oncology patients. [30][31][32][33][34][35][36][37][38][39] One of those studies reported mild, asymptomatic QT prolongations that remained within normal limits. 31 A literature search was performed for reports of ventricular arrhythmias, fatalities, or any type of toxicity thought to be related to ondansetron in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Die angewendete niedrigere Dosierung ist auch deshalb sinnvoll, weil nach Prophylaxe/Therapie mit Tropisetron, das selbst leichte QT-Verlängerungen induziert, eine pharmakodynamische Interaktion nicht sicher ausgeschlossen werden kann [9,25].…”
Section: Diskussionunclassified
“…5-HT 3 -Antagonisten eignen sich dazu nicht [14,19], und die Dexamethasongabe zu wiederholen, ist nicht sinnvoll [13]. Rescue-Medikamente sollen über andere Wirkmechanismen wie Dopamin-, Histamin-oder Neurokininrezeptoren agieren [22] [8,25,26]. Bemerkenswert ist außerdem die Tatsache, dass 5-HT 3 -Antagonisten in großem Ausmaß verabreicht werden, obwohl auch für sie schwerste Herzrhythmusstörungen beschrieben worden sind [7,24].…”
Section: Diskussionunclassified